Creative Strategies in the Recovery of Endangered Languages - Patria, Rida; Merdeka, Pijar Hatinurani (EDUPEDIA Publisher, 2023)
The endangerment and extinction of languages represent a significant loss to cultural diversity and heritage. As languages fade into obscurity, so do the unique perspectives, knowledge systems, and traditions they carry. This paper delves into the innovative and creative strategies employed in the revitalization and recovery of endangered languages. Drawing from a diverse range of case studies and linguistic research, this study examines the multifaceted approaches that linguists, educators, communities, and technology developers have adopted to reverse language decline trends. The paper begins by discussing the pressing need to preserve linguistic diversity and the inherent challenges posed by language endangerment. It then navigates through the innovative strategies that have emerged, including the integration of language revitalization programs into formal education, the cultivation of intergenerational transmission through family-centered initiatives, and the empowerment of communities through digital tools and social media platforms. Furthermore, the study highlights the role of creativity and adaptability in these efforts. It explores how language activists and experts have leveraged artistic expression, storytelling, and cultural events to instill a sense of pride and ownership within endangered language communities. The paper also underscores the symbiotic relationship between language and the arts, illustrating how music, visual arts, and literature can serve as both vehicles for language transmission and mediums through which the essence of a language can be captured. Moreover, this research investigates the utilization of modern technology in language revitalization. It showcases examples of digital dictionaries, mobile applications, and online collaborative platforms that facilitate learning, documentation, and communication in endangered languages. The potential of these tools in engaging younger generations and fostering a sense of belonging is discussed in detail.